As inovações da indústria 4.0 e os reflexos na ergonomia e segurança - Schreiber, Joseani (2020)
The fourth industrial revolution took shape at the Hannover industrial fair in 2011. It emerged from three other major historical groups of revolution, however, in return, they came looking for intelligent production, which is based on CPS principles (cyber-physical system), maintaining objectives in the context between machines and men, and not only in their fateful use. Dur-ing its development, what is called the Industry 4.0 model emerges, which is based on the communication and contribution of systems with each other and with humans, in real time, seeking to improve the performance of production processes, increase profits, decrease costs, production costs and increase the safety and ergonomics of operations. Therefore, it is a promising field of analysis for engineering and industrial financial fields. As a result, this research aimed to identify how innovations in the area of Ergonomics and Safety are helping in Industry 4.0, and how they are reflected in these two areas. At the methodological level,a bibliographic survey was carried out, which was complemented with a Field Study, by means of an interview, with an approach, respectively, analytical-expository and qualitative. We sought, from both methodologies, to confront the information of innovations present in the bibliography in view of the practical perceptions of the industrial environment, thus forming a research that presents data on the innovations and reflexes perceived in the two fields of analysis. As a result, it was found that the current industries have sought to implement innovations and have perceived pos-itive effects in the face of the new Industrial Revolution and Industry 4.0. Thus, even if the bibliographic publications bring an experimental set, or not, of innovations, these are being proposed and used in smart factories to measure the physical, mental load, stress level, simulators of workplaces designed with safety, glasses safety training, among other projects that make the relationship between Industry 4.0 and Workplace Safetya long-term scientific project in the coming years.